Therapeutic hypothermia for intracerebral hemorrhage: Systematic review and meta-analysis of the experimental and clinical literature. Issue 5 (June 2022) - Baker, Turner S; Durbin, John; Troiani, Zachary; Ascanio-Cortez, Luis; Baron, Rebecca; Costa, Anthony; Rincon, Fred; Colbourne, Frederick; Lyden, Patrick; Mayer, Stephan A; Kellner, Christopher P
Background: Intracerebral hemorrhage remains the deadliest form of stroke worldwide, inducing neuronal death through a wide variety of pathways. Therapeutic hypothermia is a robust and well-studied neuroprotectant widely used across a variety of specialties. Aims: This review summarizes results from preclinical and clinical studies to highlight the overall effectiveness of therapeutic hypothermia to improve long-term intracerebral hemorrhage outcomes while also elucidating optimal protocol regimens to maximize therapeutic effect. Summary of review: A systematic review was conducted across three databases to identify trials investigating the use of therapeutic hypothermia to treat intracerebral hemorrhage. A random-effects meta-analysis was conducted on preclinical studies, looking at neurobehavioral outcomes, blood brain barrier breakdown, cerebral edema, hematoma volume, and tissue loss. Several mixed-methods meta-regression models were also performed to adjust for variance and variations in hypothermia induction procedures. Twwenty-one preclinical studies and five human studies were identified. The meta-analysis of preclinical studies demonstrated a significant benefit in behavioral scores (ES = −0.43, p = 0.02), cerebral edema (ES = 1.32, p = 0.0001), and blood brain barrier (ES = 2.73, p ≤ 0.00001). Therapeutic hypothermia was not found to significantly affect hematoma expansion (ES = −0.24, p = 0.12) or tissue loss (ES = 0.06, p = 0.68). Clinical study outcome reporting was heterogeneous; however, there was recurring evidence of therapeutic hypothermia-induced edema reduction. Conclusions: The combined preclinical evidence demonstrates that therapeutic hypothermia reduced multiple cell death mechanisms initiated by intracerebral hemorrhage; yet, there is no definitive evidence in clinical studies. The cooling strategies employed in both preclinical and clinical studies were highly diverse, and focused refinement of cooling protocols should be developed in future preclinical studies. The current data for therapeutic hypothermia in intracerebral hemorrhage remains questionable despite the highly promising indications in preclinical studies. Definitive randomized controlled studies are still required to answer this therapeutic question.